Efficacy of some biocides against Potato Leafhopper, Empoasca fabae (Homoptera: Cicadellidae), on cowpea - Khamas, Nihad Aziz; Salim, Hussein Ali; Mutney, Hussein Ali; Hormoz, Ferial Bahgat (JOURNAL OF ADVANCES IN BIOLOGY, 2018)
A field study was carried out in Khan Bani Saad district, Diyala province on 2015 to evaluate bio pesticides viz. Spinosad (Saccharopolyspora spinosa) , BSA3 (Beauveria bassiana) , Mycotal (Lecanecillium muscarium) and using chemical insecticide Hatchi hatchi 15% EC against Potato Leafhopper Empoasca fabae on cowpea. the rate of nymphs and adults population was significantly reduced in treatments Hatchi hatchi (1.8,3.7), Mycotal (3.3,4.7) , Spinosad (3.3,5.6)and BSA3 (3.7,6.4) compared with control (6.4,9.2) respectively. The results was showed that superiority of spinosad treatment in mortality of nymphs of E. fabae to (44.76%) with significant differences from other treatments followed by mycotal (41.31%), and then BSA3, which amounts to (29.77%). Mycotal was showed high mortality in the adults of E. fabae to 50.6% then Spinosad (39.49%) and BSA3 (30.15%) . This study shows that the use of one of these biocides in the field may be sufficient to reduce the numbers of nymphs and adults during the study season.